A Theophylline-Responsive Riboswitch Regulates Expression of Nuclear-Encoded Genes. Issue 1 (8th November 2019) - Shanidze, Nana; Lenkeit, Felina; Hartig, Jörg S.; Funck, Dietmar
Abstract : Artificial, ligand-responsive RNA aptazymes are an efficient tool for dose- and time-dependent external control of nuclear gene expression in plants. Abstract: Riboswitches are small cis-regulatory RNA elements that regulate gene expression by conformational changes in response to ligand binding. Synthetic riboswitches have been engineered as versatile and innovative tools for gene regulation by external application of their ligand in prokaryotes and eukaryotes. In plants, synthetic riboswitches were used to regulate gene expression in plastids, but the application of synthetic riboswitches for the regulation of nuclear-encoded genes in planta remains to be explored. Here, we characterize the properties of a theophylline-responsive synthetic aptazyme for control of nuclear-encoded transgenes in Arabidopsis ( Arabidopsis thaliana ). Activation of the aptazyme, inserted in the 3′ UTR of the target gene, resulted in rapid self-cleavage and subsequent decay of the mRNA. This riboswitch allowed reversible, theophylline-dependent down-regulation of the GFP reporter gene in a dose- and time-dependent manner. Insertion of the riboswitch into the ONE HELIX PROTEIN1 gene allowed complementation of ohp1 mutants and induction of the mutant phenotype by theophylline. GFP and ONE HELIX PROTEIN1 transcript levels were downregulated by up to 90%, and GFP protein levels by 95%. These results establish artificial riboswitches as tools for externally controlled gene expression in synthetic biology in plants or functional crop design.